Association between injury history and performance of male elite ice hockey players - Balci, N. C.; Akbasli, O.; Dogan, I. E.; Kara, O. K. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study is to examine the relationship between past injuries and the on-ice and off-ice performance of elite male ice hockey players. This study included participation of 50 elite male ice hockey players (age 23.8 ± 5.3 years). Off-ice performance was measured by 30m Sprint Test, Broad Jump Test, Push-up Test, Hexagon Agility Test, and Plank Test, while on-ice performance was measured by 30m On-ice Sprint Test and Cornering "S" Turn Agility Test. Examination of the athletes` history of injury included their previous injury site, type, number and mechanism of injuries. In the push-up test, there was a significant difference between the athletes who had left hand and right knee injuries and those who had a dislocation injury (p <0.05). A statistically significant difference was determined between athletes who had a puck injury and who had not according to their performance on the cornering s turn agility test results(p <0.05). A statistically significant difference was also found between athletes who had an overuse injury and who had not according to their performance on the 30m sprint and hexagonagility test results(p <0.05). Lastly, there was a significant correlation between on-ice tests and off-ice broad jump, push-up and plank tests (r=-0.310-0.540; p<0.05).This study demonstrates that the push-up test could be the most effective test for determining level of performance after an athlete has suffered an injury. Furthermore, on-ice test results were shown to have a correlation with off-ice plank test results, which could bean indicator of an athlete`s core muscle strength following an injury.Keywords: Hockey,performance testing,wounds and injuries,muscular strength and endurance